Committed change of real-time quantitative PCR to droplet digital PCR for monitoring BCR::ABL1 transcripts in tyrosine kinase inhibitor treated CML - Adcharee Kongruang; Nittaya Limsuwanachot; Sutada Magmuang; Prapatsorn Areesirisuk; Pimjai Niparuck; Teerapong Siriboonpiputtana; Budsaba Rerkamnuaychoke (Hematology, 2023)
ABSTRACTObjectives We performed a feasibility study of an FDA-approved commercial ddPCR assay to measure BCR::ABL1 in CML patients treated using TKI therapy.Methods Assay performance of standard RQ-PCR and commercially available FDA-approved ddPCR were compared to measure BCR::ABL1 p210 transcripts in RNA samples from 100 CML patients who received TKI therapy.Results %BCR::ABL1/ABL1IS levels obtained from both methods were not statistically significant difference after normalization with batch-specific conversion factor (p = 0.0651). The correlation and agreement of %BCR::ABL1/ABL1IS between the two assays were high. Molecular response stratification data showed 56% concordance between RQ-PCR and ddPCR, and 37% higher residual disease detection using ddPCR. Furthermore, 21.21% (7/33) of RQ-PCR undetectable samples were detected by ddPCR, representing high sensitivity to quantify the low abundance of BCR::ABL1 transcripts.Conclusion ddPCR was proven to be a highly sensitive method with the potential to overcome some limitations of traditional RQ-PCR, and has the potential of being a valuable tool for monitoring BCR::ABL1 transcripts in CML during TKI therapy. (163 words)